Integrative Analysis of RNA Expression and Regulatory Networks in Mice Liver Infected by Echinococcus multilocularis - Liu, Tingli; Li, Hong; Li, Yanping; Wang, Liqun; Chen, Guoliang; Pu, Guiting; Guo, Xiaola; Cho, William C.; Fasihi Harandi, Majid; Zheng, Yadong; Luo, Xuenong (Frontiers in Cell and Developmental Biology, 2022)
The larvae of Echinococcus multilocularis causes alveolar echinococcosis, which poses a great threat to public health. However, few effective and safe drugs are available for the patients with E. multilocularis infection, largely relying on surgical resection with a high recurrence rate. Exploring the transcriptional baseline in the liver in response to E. multilocularis infection will help us to develop effective treatment strategies. Using liver perfusion and RNA-seq, different cell populations including the hepatic cells (HCs), hepatic stellate cells (HSCs) and Kupffer cells (KCs) were isolated, and their transcriptional profiles including lncRNAs, miRNAs and mRNAs during the infection were comparatively defined. In all three cell populations, the most differentially-expressed (DE) mRNA, lncRNAs and miRNAs were annotated to be involved in immune responses. Following integrative analysis of 38 differentially-expressed DEmiRNAs and 8 DElncRNAs, the lncRNA-mRNA-miRNA networks were constructed, including F63-miR-223-3p-Fbxw7/ZFP36/map1b and F63-miR-27-5p-Tdrd6/Dip2c/Wdfy4. These results provide foundation for further exploration of the regulatory networks during E. multilocularis infection.